Local initiative supports case isolation and contact tracing during a SARS-CoV-2 surge in summer 2020: a community case study in Antwerp, Belgium - Verdonck, Kristien; Morreel, Stefan; Vanhamel, Jef; Vuylsteke, Bea; Nöstlinger, Christiana; Laga, Marie; van Olmen, Josefien (Frontiers in Public Health, 2023)
In Antwerp, Belgium's second largest city, a COVID-19 surge in July 2020 predominantly affected neighborhoods with high ethnic diversity. Local volunteers reacted and set up an initiative to support contact tracing and self-isolation. We describe the origin, implementation, and transfer of this local initiative, based on semi-structured interviews of five key informants and document review. The initiative started in July 2020, when family physicians signaled a surge of SARS-CoV-2 infections among people of Moroccan descent. Family physicians feared that the mainstream contact tracing organized by the Flemish government through centralized call centers would not be efficient in halting this outbreak. They anticipated language barriers, mistrust, inability to investigate case clusters, and practical problems with self-isolation. It took 11 days to start up the initiative, with logistical support from the province and city of Antwerp. Family physicians referred SARS-CoV-2-infected index cases with complex needs (including language and social situation) to the initiative. Volunteer COVID coaches contacted cases, got a contextualized understanding of their living conditions, assisted with backward and forward contact tracing, offered support during self-isolation, and checked if infected contacts also needed support. Interviewed coaches were positive about the quality of the interaction: they described extensive open conversations with cases. The coaches reported back to referring family physicians and coordinators of the local initiative, who took additional action if necessary. Although interactions with affected communities were perceived as good, respondents considered that the number of referrals by family physicians was too low to have a meaningful impact on the outbreak. In September 2020, the Flemish government assigned the tasks of local contact tracing and case support to the local health system level (primary care zones). While doing so, they adopted elements of this local initiative, such as COVID coaches, tracing system, and extended questionnaires to talk with cases and contacts. This community case study illustrates how urgency can motivate people to action yet support from people with access to resources and coordination capacity is vital for effective organization and transition to long-term sustainability. From their conception, health policies should consider adaptability of new interventions to local contexts.